The Effect of Rice Husk Ash as Cement Substitution on the Compressive Strength of Self-Compacting Concrete - Putri, Prima Yane; Kamil, Insannul; Rizandi, Alfin (Universitas Negeri Padang, 2024)
Self-Compacting Concrete (SCC) is an innovative solution in today's world of concrete technology. Unlike traditional concrete, it does not require a vibrator for compaction, which makes concrete work easier. One of the key features of SCC is its high workability, which is achieved through the use of chemical admixtures and mineral additives. Rice husk ash is one such additive that can be used as a pozzolanic material for concrete mixtures, which is important as rice husk waste can cause environmental problems. The objective of this study was to investigate the effect of rice husk ash on SCC concrete. The study involved using Rice Husk Ash (RHA) as a partial replacement for cement in SCC concrete at varying percentages (0%, 5%, 10%, and 15% of cement weight). The results of the slump flow test showed that the highest value of 775 mm was achieved at 15% RHA, meeting the specifications of SCC concrete. In terms of compressive strength, the results showed that the SCC mixture without rice husk ash (0% RHA) had the highest average compressive strength, which was 30.56 MPa at 14 days and 31.66 MPa at 28 days of concrete. On the other hand, the average compressive strength of SCC concrete with rice husk ash mixture was highest at 5% RHA, with 25.04 MPa at 14 days and 28.81 MPa at 28 days. Overall, the study found that the use of rice husk ash in SCC concrete had a significant effect on its compressive strength, with the highest compressive strength being achieved at 5% RHA.